The Impact of the Quizlet App on Students' Mufradât Mastery: An Experimental Study - Ibnu Rawandhy N. Hula; Yousif Abdelmannan Mohamed Godat Arrashedy; Mohamad Lahay; Mukhtar I. Miolo; Damhuri Damhuri; Abdullah Sakka (Al-Ta'rib)
This research is motivated by the observation that 10th-grade students at MAS Al-Huda in Gorontalo City have low mastery of mufradât. This is evident from their difficulties in understanding reading materials and communicating in Arabic. Therefore, this study aims to determine whether the experimental Quizlet application has an effect on improving the mastery of mufradât among these students. The researcher employed a quantitative method using a quasi-experimental design. The study's population consisted of 40 students, and the entire population was included in the sample. Data were collected through tests, which were analyzed using (1) descriptive statistics, (2) normality tests, (3) paired sample t-tests, (4) homogeneity tests, and (5) independent sample t-tests. The results indicated that the average pre-test score for the control class was 68.25, while the average post-test score for the experimental class was 83.50. The Independent Sample t-test yielded a Sig. (2-tailed) score of 0.000, which is less than 0.05, indicating a significant difference. These findings support the hypothesis that the experimental Quizlet application significantly and positively enhances the mastery of mufradât among 10th-grade students at MAS Al-Huda in Gorontalo City. Thus, Quizlet can be considered an effective application for learning Arabic, as it provides a more engaging and enjoyable learning experience while improving students' outcomes in mufradât.